Elementary Technical Mathematics

Published by Brooks Cole
ISBN 10: 1285199197
ISBN 13: 978-1-28519-919-1

Chapter 6 - Review: 15

Answer

x=6

Work Step by Step

Simplifying 3x + -4(x + -3) = 3(x + -4) Reorder the terms: 3x + -4(-3 + x) = 3(x + -4) 3x + (-3 * -4 + x * -4) = 3(x + -4) 3x + (12 + -4x) = 3(x + -4) Reorder the terms: 12 + 3x + -4x = 3(x + -4) Combine like terms: 3x + -4x = -1x 12 + -1x = 3(x + -4) Reorder the terms: 12 + -1x = 3(-4 + x) 12 + -1x = (-4 * 3 + x * 3) 12 + -1x = (-12 + 3x) Solving 12 + -1x = -12 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 12 + -1x + -3x = -12 + 3x + -3x Combine like terms: -1x + -3x = -4x 12 + -4x = -12 + 3x + -3x Combine like terms: 3x + -3x = 0 12 + -4x = -12 + 0 12 + -4x = -12 Add '-12' to each side of the equation. 12 + -12 + -4x = -12 + -12 Combine like terms: 12 + -12 = 0 0 + -4x = -12 + -12 -4x = -12 + -12 Combine like terms: -12 + -12 = -24 -4x = -24 Divide each side by '-4'. x = 6 Simplifying x = 6
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.